1999
DOI: 10.2337/diabetes.48.10.1915
|View full text |Cite
|
Sign up to set email alerts
|

No effect of insulin on glucose blood-brain barrier transport and cerebral metabolism in humans.

Abstract: The effect of hyperinsulinemia on glucose blood-brain barrier (BBB) transport and cerebral metabolism (CMRglc) was studied using the intravenous double-indicator method and positron emission tomography using [18F]fluorodeoxyglucose as tracer (PET-FDG). Sixteen normal healthy control subjects (25 +/- 4 years old) were studied twice during a euglycemic and a euglycemic-hyperinsulinemic condition. Our hypothesis was that high physiologic levels of insulin did not affect the BBB transport or net metabolism of gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
108
3
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 11 publications
11
108
3
2
Order By: Relevance
“…Insulin crosses the blood-brain barrier via the saturable transport system (19). Some studies in subjects with normal glucose tolerance have failed to show any effect of insulin on brain glucose metabolism (20), whereas other studies have demonstrated that insulin increases CMR glu (21). However, in our study, the rise in plasma insulin and glucose concentrations after EX was reduced compared with PLC, making this an unlikely explanation for the increase in CMR glu .…”
Section: Discussioncontrasting
confidence: 73%
“…Insulin crosses the blood-brain barrier via the saturable transport system (19). Some studies in subjects with normal glucose tolerance have failed to show any effect of insulin on brain glucose metabolism (20), whereas other studies have demonstrated that insulin increases CMR glu (21). However, in our study, the rise in plasma insulin and glucose concentrations after EX was reduced compared with PLC, making this an unlikely explanation for the increase in CMR glu .…”
Section: Discussioncontrasting
confidence: 73%
“…Indeed, besides results in various tissues showing an SUV overestimation, Minamimoto et al reported a small but significant decrease of 18 F-FDG accumulation in the brains of patients with suspected renal failure, compared with healthy volunteers (11). Although the relationship between kidney disease and insulin resistance of the brain is not known, these authors discussed this particular result with the results of other investigators studying diabetes (12,13).…”
Section: Discussionmentioning
confidence: 85%
“…steroid action. These are all areas, specifically the paraventricular nucleus of the hypothalamus (13), the ventromedial hypothalamus (11,17,24), and the hindbrain (34), that have been implicated in regulating counterregulatory responses to hypoglycemia and contain E2 and P4 receptors. Central injections of E2 into hindbrain areas have been found to depress renal sympathetic drive and increase vagal nerve activity in male rats (30,32).…”
Section: Discussionmentioning
confidence: 99%